Wiley Encyclopedia of Electrical and Electronics Engineering 1999
DOI: 10.1002/047134608x.w3402
|View full text |Cite
|
Sign up to set email alerts
|

Lightning, Lightning Protection and test Standards

Abstract: The sections in this article are Cloud‐To‐Ground Lightning Lightning Damage Protection Techniques Test Standards

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2013
2013

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…The heat capacity for the CNF was set to 0.716 J/(g K), assuming it is similar to that of graphite, 43 while the heat capacity of epoxy was set to 1.06 J/(g K). 44 The values used for density were 1.80 and 1.17 g/cm 3 for CNF and epoxy, respectively. 45,46 For the Fourier method, constant temperature boundary conditions were maintained at each surface, with the top surface being kept at 310 °C and the bottom surface at 300 °C.…”
Section: Solution Methodologymentioning
confidence: 99%
See 1 more Smart Citation
“…The heat capacity for the CNF was set to 0.716 J/(g K), assuming it is similar to that of graphite, 43 while the heat capacity of epoxy was set to 1.06 J/(g K). 44 The values used for density were 1.80 and 1.17 g/cm 3 for CNF and epoxy, respectively. 45,46 For the Fourier method, constant temperature boundary conditions were maintained at each surface, with the top surface being kept at 310 °C and the bottom surface at 300 °C.…”
Section: Solution Methodologymentioning
confidence: 99%
“…However, even though the main function of these composites is structural, they can be exposed to large temperature fluctuations, such as when subjected to lightning strikes. It has been reported that the nature of lightning strikes consists of multiple high current (up to 80 kA) short pulses (∼0.25–200 ms), , which can generate large heat fluxes in the composite. Addressing fiber composite behavior when subjected to a short heat pulse of large magnitude is of significant importance due to the possibility of thermal degradation within the composite. , Therefore, developing thermally conductive nanocomposite materials to be used for heat dissipation and structural protection is of significant value.…”
Section: Introductionmentioning
confidence: 99%